Alcohol consumption among university students in Ireland and the United Kingdom from 2002 to 2014: a systematic review. (December 2016) - Davoren, Martin; Demant, Jakob; Shiely, Frances; Perry, Ivan
Abstract Background Alcohol is a leading cause of global suffering. Europe reports the uppermost volume of alcohol consumption in the world, with Ireland and the United Kingdom reporting the highest levels of binge drinking and drunkenness. Levels of consumption are elevated among university students. Thus, this literature review aims to summarise the current research on alcohol consumption among university students in the Republic of Ireland and the United Kingdom. Methods MEDLINE, CINAHL, EMBASE and PsychInfo were systematically searched for literature from January 2002 until December 2014. Each database was searched using the following search pillars: alcohol, university student, Ireland or the United Kingdom and prevalence studies. Results Two thousand one hundred twenty eight articles were retrieved from electronic database searching. These were title searched for relevance. 113 full texts were retrieved and assessed for eligibility. Of these, 29 articles were deemed to meet inclusion criteria for the review. Almost two thirds of students reported a hazardous alcohol consumption score on the AUDIT scale. Over 20 % reported alcohol problems over their lifetime using CAGE while over 20 % exceed sensible limits each week. Noteworthy is the narrowing of the gender gap throughout the past decade. Conclusion This is the first review to investigate consumption patterns of university students in Ireland and the United Kingdom. A range of sampling strategies and screening tools are employed in alcohol research which preclude comparability. The current review provides an overview of consumption patterns to guide policy development.